The marine record of the onset of farming around the Arabian Sea at the dawn of the Bronze Age. (June 2020) - Gourlan, Alexandra T; Albarede, Francis; Achyuthan, Hema; Campillo, Sylvain
The rise and fall of human cultures are strongly modulated by the strong environmental changes taking place during the Holocene. Here, we use the sedimentological and geochemical records of a core taken in the Arabian Sea, west of Kerala, to identify potential factors that may reflect on-land history of local civilizations, in particular the Harappan culture which appeared and collapsed in the Indus Valley during the early and middle Bronze Age. The 14 C record highlights a fourfold increase in sedimentation rate at 5380 cal. yr BP. The short duration of this event ( 220 years) suggests a steep regional increase in erosion at the beginning of the Bronze Age. Factor analysis of downcore changes in geochemistry identified two distinct detrital components dominated by silt and clay, respectively, and a component characteristic of chemical erosion. This interpretation is consistent with sediment mineralogy. Comparison with the known climatic record indicates that increased erosion rate at 5380 cal. yr BP around the Arabian Sea is because of the advent of farming. The development of tillage associated with both wheat and barley crops and animal husbandry was favored by trade between Mesopotamia and India. Human activities, therefore, were the trigger of major changes in the sedimentological and geochemical records at sea at the onset of the Bronze Age.